PENGARUH TINGKAT PENAMBAHAN BAHAN PENGAWET TERHADAP KADAR BAHAN KERING DAN PERSENTASE KEBERHASILAN SILASE RUMPUT Panicum sarmentosum Robx - Saloko, Fatmawati (AgriSains, 2005)
The addition of preservatives may result in better quality of silage.  This experiment was aimed to examine the effects of addition of preservative on dry matter and success percentage of Panicum sarmentosum silage. The preservative used were rice bran, corn bran and salt with composition of 50, 48 and 2%, respectively. The completely randomized design was employed in this experiment with 6 treatments and 3 replicates.  The treatments were addition of preservatives at concentation of 0, 7.5; 15; 22.5; 30 and 37.5% of the grass weight.  The parameters measured were dry matter content of the silage and the degree of the success of silage. The result showed that the concentation of addition of preservative influenced significantly dry matter and the percentage of the success of silage.  However, at concentation of 22.5% of the grass weight resulted in the highest dry matter and degree of success of Panicum sarmentosum silage. Date suggested that moderate concentation of the preservatives was sufficient to increase the dry matter content and the degree of success of Panicum sarmentosum silage. Key words : Dry matter, silage, Panicum sarmentosum Robx